Influence of Different Immersion Solutions and Polishing Protocols on the Roughness of Conventional and CAD/CAM Restorative Materials - Lorenzetti, Camila Cruz [UNESP]; Silva, Aryvelto Miranda; Castro-Núñez, Gabriela Mariana; Viola, Kennia Scapin [UNESP]; Bortolatto, Janaína Freitas; de Campos, Edson Alves [UNESP]; Saad, José Roberto Cury [UNESP] (FapUNIFESP (SciELO), 2025)
Objective: To evaluate the effects of immersion solutions and polishing protocols on the surface roughness of different restorative materials. Material and Methods: Specimens from composite resin (CR) (Filtek Z350 XT) and CAD-CAM blocks of resin nanoceramic (NC) (Lava Ultimate Restorative), hybrid ceramic (HC) (Enamic), and zirconia-reinforced lithium silicate (ZL) (Celtra Duo) were assigned to two protocols: only polishing rubbers (PR) (Ceramisté rubbers®) or PR + paste (Porcelize®) (PR+P). Surface roughness was measured before (T0), after 30 days (T1), and 60 days (T2) of immersion in solutions of artificial saliva (SA), coffee (CF), and Coca-Cola® (CO). Roughness changes were compared using ANOVA and Tukey test (α=0.05). Results: Time (p≤0.003) and the interaction of time and immersion solution (p≤0.03) significantly affected all materials. The interaction of time, immersion solution, and polishing significantly affected ZL (p=0.003) and NC (p=0.013). The highest surface roughness values were observed with CF solution at T2. Conclusion: Different polishing protocols did not significantly affect the restorative materials tested. The CF solution affected the surface roughness of composite resin and feldspathic-composite hybrid ceramic after 60 days, regardless of the polishing protocol. The effects of immersion solutions and polishing protocols vary and depend on the properties of each restorative material.
Keywords: Ceramics; Composite Resins; Computer-Aided Design; Dental Polishing; Surface Properties